Brief cognitive behavioral therapy for depression among patients with alcohol dependence in Thailand - Thapinta,D. (Informa Healthcare, 2015)
This study evaluated the short-term efficacy of brief cognitive behavioral therapy for reducing depression among Thai general hospital patients with alcohol dependence. A quasi-experimental design was used with a control group and pretest, posttest, and follow-up assessments. Participants were patients with alcohol dependence and depression who were recruited from district and provincial hospitals in northern Thailand. Eighty (N = 80) eligible participants were purposively selected and enrolled, and then randomly assigned into two groups. One group received three weeks of brief six-session cognitive behavioral therapy as the intervention, and the other group received usual care as their treatment. Data were collected at Week 0 (pretest), Week 3 (posttest), and Week 7 (one month follow-up) and included a nine-item depression scale, with analysis through descriptive statistics and t-test. Findings indicated that the mean depression scores decreased significantly (p <.01) in both the experimental (n = 33) and control groups (n = 27) at the one month follow-up (Week 7). However, only the experimental group showed significant differences in their mean depression scores between pre-and posttest. At Week 7, the experimental group showed significantly lower mean depression scores than the control group (p <.05). In summary, the brief six-session cognitive behavioral therapy intervention yielded promising results and may benefit patients with alcohol dependence and depression who are seen in general hospital settings. © 2014 Informa Healthcare USA, Inc.